Student activation in theoretical physics lectures - Olaf Haerter, Jan (Improving University Science Teaching and Learning, 2023)
For theoretical courses, such as in physics or mathematics, it continues to often be common, to present lecture material in a blackboard-type format. This study addresses the question, if students of such courses might perceive this teaching style outdated, as many other presentation styles are possible. To this end, it was addressed, whether students of theoretical physics would prefer more student activation, that is, direct student participation in lectures. They were also asked to describe, in how far they would benefit from pre-recorded lectures, available before the actual class date, or from other forms of presentation, such as slide show performances. The results obtained were quite clear: for the type of lecture in question, 27 respondents mostly found that (i) blackboard presentations were the preferred teaching style; (ii) moderate student activation is useful in internalizing the teaching material; and (iii) replacing lectures by additional exercises, yielding more student activity would not be advisable, even if lectures were pre-recorded and available through the web.